Angklung Tradisional Sebagai Sumber Belajar Sejarah Lokal - Sumaludin, M. Maman (Prabayaksa: Journal of History Education, 2022)
Traditional angklung in the life of sundanese people bequeathed local wisdom that deserves to be studied amid globalization today. The study describes traditional angklung as a non-material cultural heritage in local historical learning. Learn this method of using descriptive qualitative approaches with data collection techniques using interviewing, observation, and literature studies. Research results show that angklung as a non-material World Heritage designated by UNESCO on November 16, 2010, is a tool art traditional at first as part of the ritual ceremony later keep going evolved and adapt with changing times to become art that is functional for entertainment. Traditional angklung with pentatonic tones can still be found in some indigenous villages or indigenous peoples as well as traditional angklung art groups in West Java and Banten such as Angklung Kanekes, Angklung Dogdog Lojor, Kacang Angklung, Angklung Badeng, Angklung Gubrag, and Angklung Bungko, and Angklung Dodod. Angklung is a form of non-material culture that has the potential as a source of local history whose values deserve to be passed on to the millennial generation. Values in traditional angklung such as religion, cooperation, discipline, responsibility, tolerance, and caring become the basis of character formation in harmony with the skills needed in the 21st century, namely the ability to think (critical thinking, creativity, problem-solving), the ability to cooperate (collaboration, communication), the ability to behave (feeling management), as provisions for future Millennials.